Penanggulangan Terhadap Penyalahgunaan Zat Adiktif Inhalan (LEM) - I Kadek Buana Putra Sedana; I Nyoman Gede Sugiarta; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2021)
The abuse of inhalant addictive substances does not have specific rules governing the perpetrator of abuse that causes disruption of public order and comfort by the effects of these substances so that they can harm the surrounding community and can also threaten the life of the user at the same time if used sustainably. This study aims to explain the legal sanctions given to perpetrators of inhalant addictive substance abuse and to describe the efforts to overcome the occurrence of inhalant addictive substance abuse. This study was designed using normative legal research with a statutory approach, namely conducting research from library materials or secondary data and conducting research on the prevention of inhalant addictive substance abuse. The data sources used were primary, secondary, and tertiary legal data. The results showed that the abuse of inhalant addictive substances did not have specific rules, but in the Criminal Code and the Law, the impacts and risks of abuse with minors, then to overcome the abuse of inhalant addictive substances, can use non-criminal legal policy measures (Non-Penal) and criminal law policy (Penal).